Procalcitonin is a predictive marker for severe acute pancreatitis - Bülbüller, Nurullah; Do?ru, Osman; Ayten, Refik; Akbulut, Handan; Ilhan, Yavuz Selim; Çetinkaya, Ziya (My University, 2006)
BACKGROUND: Early identification of patients who develop severe acute pancreatitis and those who can benefit from intensive care is important. We studied whether procalcitonin, a marker of systemic inflammation, is important in the differential diagnosis of patients with mild and severe acute pancreatitis. METHODS: Patients were divided into two groups (mild and severe form) prospectively. Procalcitonin levels and the Ranson's and Acute Physiology and Chronic Health Evaluation II scores were determined both at admission and during the follow-up. RESULTS: Of the 65 patients with acute pancreatitis, 46 had mild and 19 had severe pancreatitis. Sensitivity and specificity values for patients calculated using procalcitonin level at 0.5 ng/ml, Ranson's score at 3 and APACHE II score at 8 cut-off levels, were 100%, 84% and 89%; and 84%, 63% and 89% respectively. CONCLUSION: Procalcitonin is a practical, simple parameter that can be used in order to diagnose severe acute pancreatitis earlier and to monitor the clinical prognosis of the disease.
Keywords: APACHE II; Pancreatitis/blood/diagnosis; Procalcitonin; Prognosis